2023
DOI: 10.5530/ijper.57.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Educational Programs on the Knowledge and Attitude of Healthcare Professionals in Antimicrobial Stewardship

Abstract: Introduction:The main concern related to antimicrobial use is the increasing incidence of resistance. Objective: This study aims to assess the impact of educational programs on the knowledge, attitudes, and practices of healthcare providers concerning antimicrobial Stewardship (AMS) in hospitals. Materials and Methods: This is a quasi-experimental study with one group pretest-posttest design. Health professionals were requested to complete an online questionnaire before and after educational programs. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a study conducted at the National Liver Institute, Egypt, an educational program was offered to healthcare providers as an intervention to the ASP, and improvement in the knowledge, attitude, and practice of healthcare providers was observed as a result of the intervention (Tahoon et al, 2020). Various other studies have also shown significant improvements in the rational utilization of antibiotics after the educational intervention, particularly led by pharmacists (Monmaturapoj et al, 2021;Lai et al, 2022;Otieno et al, 2022;Xu et al, 2022;Almutairi et al, 2023;Lutfiyati et al, 2023). The ASP requires multidisciplinary healthcare workers to perform as a single unit, and education based on updated information is a requisite for informed decision making (Laxminarayan et al, 2013;Cosgrove et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted at the National Liver Institute, Egypt, an educational program was offered to healthcare providers as an intervention to the ASP, and improvement in the knowledge, attitude, and practice of healthcare providers was observed as a result of the intervention (Tahoon et al, 2020). Various other studies have also shown significant improvements in the rational utilization of antibiotics after the educational intervention, particularly led by pharmacists (Monmaturapoj et al, 2021;Lai et al, 2022;Otieno et al, 2022;Xu et al, 2022;Almutairi et al, 2023;Lutfiyati et al, 2023). The ASP requires multidisciplinary healthcare workers to perform as a single unit, and education based on updated information is a requisite for informed decision making (Laxminarayan et al, 2013;Cosgrove et al, 2014).…”
Section: Introductionmentioning
confidence: 99%